Allele-specific silencing of dominant disease genes - Miller, Victor M. (National Academy of Sciences, 2003)
Small interfering RNA (siRNA) holds therapeutic promise for silencing dominantly acting disease genes, particularly if mutant alleles can be targeted selectively. In mammalian cell models we demonstrate that allele-specific silencing of disease genes with siRNA can be achieved by targeting either a linked single-nucleotide polymorphism (SNP) or the disease mutation directly. For a polyglutamine neurodegenerative disorder in which we first determined that selective targeting of the disease-causing CAG repeat is not possible, we took advantage of an associated SNP to generate siRNA that exclusively silenced the mutant Machado–Joseph disease/spinocerebellar ataxia type 3 allele while sparing expression of the WT allele. Allele-specific suppression was accomplished with all three approaches currently used to deliver siRNA: in vitro-synthesized duplexes as well as plasmid and viral expression of short hairpin RNA. We further optimized siRNA to specifically target a missense Tau mutation, V337M, that causes frontotemporal dementia. These studies establish that siRNA can be engineered to silence disease genes differing by a single nucleotide and highlight a key role for SNPs in extending the utility of siRNA in dominantly inherited disorders.